“Gestión De Prevención Del Consumo De Bebidas Alcoholicas En El Personal Militar Activo Que Acude Al Hospital Naval De Guayaquil, De Julio A Diciembre De 2013” - Rivas Cún, Mary Esther (2015)
Alcohol consumption is recognized as a social problem in all countries and for its easy access in all ages, is a major cause of domestic violence and traffic accidents; the problem identified in the present study is the excessive consumption of alcohol among military naval force, resulting in family problems, illness, accidents, among others; This study aims to describe alcohol consumption among users attending the Naval Hospital, to outline strategies that allow for timely promotion and prevention of alcohol intake to said user group; as a descriptive research design methodology, retrospective, which identified the behavior of the group under study was conducted, the sample was 172 users, who were applied a survey; between the results obtained it can be mentioned that: it is in males (92%) which mainly alcohol problems arise; regarding the age at which this disorder occurs is very young (56%) between 18 and 35 years of age, although there is also an equally high number from 36 to 45 years (34%); the range of the staff of this institution went to the troops (80%); who they have drunk or drink any alcoholic beverage (90%), among the drinks of choice is beer (70%); It has the (80%) knowledge that alcohol is harmful to health; The (80%) had problems of domestic violence consequences of alcoholism; the (92%) have had traffic accidents by intoxication; the (76%) would like to participate in an alcohol prevention program. As proposal arises conduct a prevention education program for all staff of this institution, with application of social learning. The management in the prevention of alcohol consumption is an issue that concerns the health personnel and therefore the health services manager.